Short nights of the Shadow Catcher : the epic life and immortal photographs of Edward Curtis - Egan, Timothy (Houghton Mifflin Harcourt, 2012)
"Edward Curtis was dashing, charismatic, a passionate mountaineer, a famous photographer--the Annie Liebowitz of his time. And he was thirty-two years old in 1900 when he gave it all up to pursue his great idea: He would try to capture on film the Native American nation before it disappeared. At once an incredible adventure narrative and a penetrating biographical portrait, Egan's book tells the remarkable untold story behind Curtis's iconic photographs, following him throughout Indian country from desert to rainforest as he struggled to document the stories and rituals of more than eighty tribes. Even with the backing of Theodore Roosevelt and J.P. Morgan, it took tremendous perseverance--six years alone to convince the Hopi to allow him into their Snake Dance ceremony. The undertaking changed him profoundly, from detached observer to outraged advocate. He would die penniless and unknown in Hollywood just a few years after publishing the last of his twenty volumes. But the charming rogue with the grade-school education had fulfilled his promise--his great adventure succeeded in creating one of America's most stunning cultural achievements."--